The Effect of Tax Avoidance towards Firm Value with Politic Connection as Moderating Variable - Nurul FAJRIATI; Siti NURYANAH (Communications of International Proceedings, 2020)
This study aims to examine the effect of tax avoidance towards firm value with politic connection as moderating variable. The sample consists of firms that are listed in Indonesia Stock Exchange for periods 2012-2014. The results show that, first, tax avoidance increases firm value. Second, tax avoidance decreases the agency cost. These results contrast to previous studies. The results indicate that in Indonesia tax avoidance is considered as an activity approved by the principal, so it will not cause the agency problem and agency cost. This research also shows a different result with previous studies, where political connection can weaken the effect of tax avoidance against firm value. This result indicates further that political connections will causing a lack of innovation and decrease the company's performance.
Keywords: Tax avoidance; politic connection; firm value and agency cost.